STRATEGI PENGEMBANGAN KOMUNIKASI MASYARAKAT KELOMPOK TANI QORYAH TOYYIBAH DI KALIBENING KECAMATAN TINGKIR KOTA SALATIGA - Ilyas Ilyas (INJECT (Interdisciplinary Journal of Communication), 2016)
This research was aimed to reveal strategy of society communication development  within Qoryah Thoyyibah farmer association, through the farmer effort to increase organic rice plant commodity. This  research  used  descriptive  qualitative  approach  and  method  where  the  data  were  collected through observation, interview, documentation, and it also used triangulation of resource, data, and theory.  The  research  subjects  were  the  member  and  the  committee  of  Qoryah  Toyyibah  farmer association at Kalibening, Tingkir  district of Salatiga city. Through society empowerment, farmer association  of  organic  rice  plant  commodity  economically  has  raised  their  welfare  better  through cooperatives  system  where  it  becomes  the  alternative  activity  in  management  especially  about financial that involves farmer crop starting from planting process, maintenance process, up to crop yield management. Moreover, the strategy of society communication of farmer association was able to  strengthen  the  friendship  among  the  member  by  implementing   Javanese  culture  philosophy, mutual assistance, friendly and peaceful communication in monthly meeting conducted. Abstrak Abstrak Penelitian bertujuan mengungkap strategi pengembangan komunikasi masyarakat Kelompok Tani Qoryah Toyyibah melalui usaha para petani untuk meningkatkan komoditas tanaman padi organik. Metode yang digunakan kualitatif diskritif, melalui observasi, wawancara, dokumentasi, dengan menggunakan trianggulasi sumber, data, dan teori. Subjek telitinya adalah anggota dan pengurus kelompok tani Qoryah Toyyibah di Kalibening Kecamatan Tingkir Kota Salatiga. Melalui pemberdayaan masyarakat kelompok tani komoditas tanaman padi organik ini secara ekonomis meningkatkan kesejahteraan dengan hasil yang baik melalui sistem perkoperasian sebagai wadah aktifitas dalam manajemen terutama masalah keuangan. Berangkat dari proses menjelang penanaman, proses perawatan, sampai manajemen hasil panen, selain, strategi komunikasi masyarakat mampu mempererat tali silaturahim antaranggota, dengan selalu menjunjung tinggi nilai falsafah budaya Jawa, gotong royong, guyub, rukun dalam bentuk dan cara diadakannya pertemuan rutin bulanan.